Structure, Electronic And Vibrational Study of 7-Methyl-2,3-Dihydro-(1,3)Thiazolo(3,2-A) Pyrimidin-5-One by Using Density Functional Theory - Joshi, Bhawani Datt; Khadka, Janga Bahadur; Bhatt, Atamram (Journal of Institute of Science and Technology, 2018)
We have presented molecular structure and vibrational wavenumber assignments of 7-methyl-2,3-dihydro-(1,3)thiazolo(3,2-a)pyrimidin-5-one. Both ab initio Hartree-Fock and density functional theory employing 6-311++G(d,p) basis set have been used for the calculations. The scaled values of the calculated vibrational frequencies were used for assignments on the basis of potential energy distribution. The structure-activity relation has been interpreted by mapping molecular electrostatic potential surface. Electronic properties have been analyzed by using time dependent density functional theory (TD-DFT) for both gaseous and solvent phase. The calculated HOMO (highest occupied molecular orbital) and LUMO (lowest unoccupied molecular orbital) energy values show that the charge transfer occurs within the molecule. Journal of Institute of Science and Technology Volume 22, Issue 2, January 2018, Page: 1-11